2021
DOI: 10.1002/1348-9585.12199
|View full text |Cite
|
Sign up to set email alerts
|

Type and timing of exercise during lunch breaks for suppressing postprandial increases in blood glucose levels in workers

Abstract: Objectives Suppression of postprandial hyperglycemia may aid in preventing lifestyle‐related diseases in working people. The present study aimed to identify the types and timings of exercises that can be performed by working people during a 60‐minute lunch break that are effective in attenuating postprandial increases in blood glucose levels. Methods Healthy working people aged 20 years and older were subjected to aerobic (AER) or resistance (RES) exercise before (Pre) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
(20 reference statements)
2
7
0
Order By: Relevance
“…This attenuation of the post-meal glucose peak has implications for the reduction in the cardiometabolic disorders associated with it, as suggested by the reduction in the levels of markers associated with oxidative stress [ 36 ]. Our results extend previous findings on the effectiveness of postprandial exercise in reducing the post-meal glycemic peak [ 8 , 14 , 16 ] to meals characterized by different CHO levels and contents of macronutrients. This constitutes a step forward for suggesting the implementation of a 30 min postprandial moderate walk in daily life scenarios, where the meal content and composition may substantially vary.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This attenuation of the post-meal glucose peak has implications for the reduction in the cardiometabolic disorders associated with it, as suggested by the reduction in the levels of markers associated with oxidative stress [ 36 ]. Our results extend previous findings on the effectiveness of postprandial exercise in reducing the post-meal glycemic peak [ 8 , 14 , 16 ] to meals characterized by different CHO levels and contents of macronutrients. This constitutes a step forward for suggesting the implementation of a 30 min postprandial moderate walk in daily life scenarios, where the meal content and composition may substantially vary.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, moderate-intensity walking appears to be a feasible exercise option for everyone as it can easily be performed without the need for any equipment and supervision of an exercise specialist. Importantly, postprandial walking has been proven effective for improving glycemic response to different meals of the day (i.e., breakfast, lunch, and dinner) both in healthy and diabetic individuals [ 8 , 11 , 14 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, breakfast included milk and cornflakes [19] while in the other study, a meal replacement drink was ingested [12]. Dinner was either an Italian pasta-based meal [17] or participants were able to choose between four different meals with matched caloric content [18].Three studies included a total number of 69 participants without type 2 diabetes and analyzed the effect of moderate-intensity treadmill walking for 20 [20] and 30 min [11,21], the effect of bodyweight resistance exercise for 20 min [20] and 7 min [11], and the effect of standing upright for 30 min [11]. Two studies compared the effect of resistance exercise and walking [11,20] and one of these studies reported a greater impact of walking compared with bodyweight resistance exercise [20].…”
Section: Results and Characteristics Of Individual Studiesmentioning
confidence: 99%
“…Again, the time intervals between meal and exercise varied between studies. Although all studies on healthy participants [11,20,21] applied designs in which exercise before meal ingestions ended immediately before eating, the time interval between meal ingestion and exercise in the postprandial state varied between 0 and 30 min. Only one of the included studies analyzed the impact of exercise-meal timing in healthy subjects and detected a greater impact of exercise immediately after meal ingestion on postprandial glucose compared with the effect of exercise 30 min after meal ingestion [11].…”
Section: Results and Characteristics Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation